2022
DOI: 10.1371/journal.pone.0264947
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 induced emergency remote instruction on students’ academic performance at an HBCU

Abstract: The outbreak of the COVID-19 pandemic early in 2020 forced universities to shut down their campuses and transition to emergency remote instruction (ERI). Students had to quickly adapt to this new mode of instruction while dealing with all other distractions caused by the pandemic. This study integrates extensive data from students’ institutional records at a large Historically Black College and University (HBCU) institution with data from a students’ survey about the impact of COVID-19 on learning during the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Of these, learner characteristics, e.g., proactiveness, self-study ability, and compliance, are the most important factors [50]. The academic results of students who attended at least one academic year of face-to-face learning before the outbreak of the pandemic were better than students who started their studies online [51]. In another study on K-12 students, low-performing students showed greater improvements in performance than high-performing students, suggesting that online learning had different effects and narrowed the gap between lowand high-performing students [52].…”
Section: Online Remote Learning During the Covid-19 Pandemicmentioning
confidence: 99%
“…Of these, learner characteristics, e.g., proactiveness, self-study ability, and compliance, are the most important factors [50]. The academic results of students who attended at least one academic year of face-to-face learning before the outbreak of the pandemic were better than students who started their studies online [51]. In another study on K-12 students, low-performing students showed greater improvements in performance than high-performing students, suggesting that online learning had different effects and narrowed the gap between lowand high-performing students [52].…”
Section: Online Remote Learning During the Covid-19 Pandemicmentioning
confidence: 99%
“…Modalities of learning environment changes such as distanced seating configurations, hybrid schedules, and reduced class sizes are widely used to maximize in-person opportunities while minimizing the risk of SARS-CoV-2 transmission by decreasing student contact [ 34 38 ]. Notably, distance learning has been reported to create significant challenges for students, particularly those of low- and middle-income backgrounds or those who rely on on-campus facilities and services for accessible technology, quiet space, or stable housing [ 39 – 42 ]. Reasons for preference in learning method are complex and are beyond the scope of this research; however, factors such as logistic capabilities, funding, local politics, and perceptions of distance learning may have played roles in decision making [ 2 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modalities of learning environment changes such as distanced seating configurations, hybrid schedules, and reduced class sizes are widely used to maximize in-person opportunities while minimizing the risk of SARS-CoV-2 transmission by decreasing student contact (3034). Notably, distance learning has been reported to create significant challenges for students, particularly those of low- and middle-income backgrounds or those who rely on on-campus facilities and services for accessible technology, quiet space, or stable housing (35–38). Reasons for preference in learning method are complex and are beyond the scope of this research; however, factors such as logistic capabilities, funding, local politics, and perceptions of distance learning may have played roles in decision making (2, 39, 40).…”
Section: Discussionmentioning
confidence: 99%
“…Modalities of learning environment changes such as distanced seating configurations, hybrid schedules, and reduced class sizes are widely used to maximize in-person opportunities while minimizing the risk of SARS-CoV-2 transmission by decreasing student contact (30)(31)(32)(33)(34). Notably, distance learning has been reported to create significant challenges for students, particularly those of low-and middle-income backgrounds or those who rely on on-campus facilities and services for accessible technology, quiet space, or stable housing (35)(36)(37)(38).…”
Section: Main Findingsmentioning
confidence: 99%